Catalytic formation of C(sp3)–F bonds via decarboxylative fluorination with mechanochemically-prepared Ag2O/TiO2 heterogeneous catalysts. Issue 48 (12th June 2017) - Tarantino, G.; Botti, L.; Dimitratos, N.; Hammond, C.
Abstract : Mechanochemically-prepared, Ag2 O-containing solid materials, are shown to be efficient heterogeneous catalysts for the synthesis of C(sp 3 )–F bonds via decarboxylative fluorination. Abstract : Mechanochemically-prepared, Ag2 O-containing solid materials, are shown to be efficient heterogeneous catalysts for the synthesis of C(sp 3 )–F bonds via decarboxylative fluorination. Five catalytic cycles without loss of intrinsic activity could be performed with the optimal catalyst, composed of 1 wt% Ag2 O supported on TiO2 (P25), despite the challenging conditions. The catalyst is easily prepared from the corresponding oxides in 20 minutes by simple mechanical mixing methods. In addition to ease of separation and re-use, the turnover numbers obtained over the solid catalyst are over one order of magnitude higher than those obtained with the state-of-the-art homogeneous catalyst, AgNO3, under otherwise identical conditions. To the best of our knowledge, this represents the first true heterogeneous catalyst for the selective formation of C(sp 3 )–F bonds with electrophilic fluorine donors, representing a major breakthrough in the field of catalytic fluorination.